Development of Comic-Based Learning Media for Javanese Language at the Junior High School Level - Khasanah, Anida Dwi Nur; Yuwono, Agus; Supriadi, Didik (Jurnal Paedagogy, 2025)
This study aims to develop Javanese comic-based learning media (KOBAJA) for teaching the topic of unggah-ungguh (Javanese language etiquette). The research employed a Research and Development (R&D) design using the 4D model, which includes the stages of definition, design, development, and dissemination. The developed product was evaluated for its feasibility through validity tests using expert validation questionnaires. Data were analyzed using both qualitative and quantitative descriptive techniques. The validity test involved both media and material experts. Product trials were conducted with students to assess the attractiveness and effectiveness of the developed media using a response questionnaire. A total of 32 Grade VII students from SMP Negeri 38 Semarang participated in the product trials. The results indicated that the developed Javanese comic (KOBAJA) is suitable for use as a reading aid and meets the required criteria. Validation from material experts yielded a score of 3.09 (“feasible to use”), while media experts gave a score of 3.5 (“very feasible”). Furthermore, student response data showed that KOBAJA was considered “very interesting” to use, with an average score of 3.44. Based on these findings, it can be concluded that the Javanese comic-based learning media (KOBAJA) is both feasible and engaging for classroom learning on unggah-ungguh topics.